تقييد الجرح بالحركات: حركة الأيدي أنموذجًا - Maulana La Eda (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This study aims to determine the jarh of scholars by using gestures، specifically hand movements. This research is a type of qualitative descriptive research with library research techniques. Among the results of the research found are: first، the texts of the ulama jarh wa ta'dil using movement are numerous and can be found in the books of hadith، rijal، 'ilal، sualat، jarh wa ta'dil، and other sources other primers. Second، the various methods of jarh wa ta'dil scholars in their jarh towards narrators by using gestures، and through this research three main movements of the scholars were found، namely: hand movements، head movements، and changes in facial expressions. As for the forms in detail، found 14 movements. Third، most of the movements used by jarh wa ta'dil scholars in their jarh are hand movements with the eight variations mentioned in this study.